2012
DOI: 10.1007/s12185-012-1233-4
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic recovery following chemotherapy is improved by BADGE-induced inhibition of adipogenesis

Abstract: This study was designed to investigate the role of increased adipocytes in the bone marrow (BM) niche induced by high-dose chemotherapy in hematopoietic recovery. Arabinosylcytosine (Ara-C) was administered to adult C57BL/6J mice to induce adipogenesis in the BM. We investigated the effects of adipogenesis on hematopoietic recovery following chemotherapy, using the peroxisome proliferator-activated receptor gamma inhibitor, bisphenol A diglycidyl ether (BADGE). Adipocyte hyperplasia could be induced by Ara-C t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 45 publications
4
56
1
1
Order By: Relevance
“…Our group has previously investigated adipogenesis induced by Ara-C and the effect of PPARγ inhibitor on hematopoietic recovery after chemotherapy [9]. As ROS mediate adipocyte differentiation in vitro and adipocytes in BM are derived from the differentiation of MSCs, whether the antioxidant NAC diminishes adipogenesis induced by Ara-C treatment was further examined in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has previously investigated adipogenesis induced by Ara-C and the effect of PPARγ inhibitor on hematopoietic recovery after chemotherapy [9]. As ROS mediate adipocyte differentiation in vitro and adipocytes in BM are derived from the differentiation of MSCs, whether the antioxidant NAC diminishes adipogenesis induced by Ara-C treatment was further examined in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have uncovered the role of adipocytes in actively suppressing hematopoiesis rather than passively filling the space of damaged BM [7,8]. In addition, previous studies by our research group have demonstrated that adipocyte hyperplasia can be induced by arabinosylcytosine (Ara-C) treatment, while bisphenol A diglycidyl ether (BADGE), a peroxisome proliferator-activated receptor gamma inhibitor), contributes to improved hematopoietic recovery after chemotherapy by inhibiting adipogenesis [9]. Therefore, the increase in adipocytes induced by chemotherapeutic drugs may play a negative role in hematopoietic recovery following chemotherapy and HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…Naveiras et al (2009) demonstrated that fat cells in the bone marrow can negatively regulate hematopoietic stem cells. The presence of a number of fat cells in the bone marrow can inhibit hematopoietic reconstruction of hematopoietic stem cells after transplantation, while inhibition of mouse marrow fat after chemotherapy can promote hematopoietic recovery (Zhu et al, 2013). In contrast, chronic blood loss in premenopausal women can stimulate marrow hematopoiesis, while marrow fat diseases such as osteoporosis typically develop in postmenopausal women (Gurevitch et al, 1999), indicating that marrow hematopoiesis in the body may also respond to the bone marrow microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…69,140 Hematopoietic recovery is improved following chemotherapy in mice with chemically inhibited adipogenesis. 141 In mouse tail vertebrae, where BM cavities are densely filled with adipocytes, the few HSCs detected are largely quiescent. 136 The adipocyte suppressive function has been attributed to the reduced production of granulocyte colony-stimulating factors (GM-CSF and G-CSF) and to the increased secretion of lipocalin-2 and neuropilin.…”
Section: Heterogeneity Of Cells Of the Nichementioning
confidence: 99%